In vivo Wound Healing Potential of Raloxifene Nanoemulsion Gel for the Management of Postmenopausal Cutaneous Wounds - Singh, Tej Pratap; Verma, Navneet; Ahmad, Farhan Jalees; Chandra, Phool; Jain, Gaurav Kumar (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Depletion in estrogen level(s) especially in postmenopausal women is reported to have delayed wound healing effects; hence we have evaluated the wound healing potential of raloxifene in rat model. Objectives: Investigating the wound healing effects of raloxifene nanoemulsion for the management of postmenopausal cutaneous wounds. Materials and Methods: The optimized nanoemulsion gel contains 0.072% raloxifene hydrochloride. Female Wistar rats were used to investigate its wound healing effects. After three months of ovariectomy, wound healing effect was observed in terms of breaking strength, tensile strength, area of wound contraction, wound closure time, hydroxyproline content and histopathological changes. Results: The nanoemulsion gel exhibited better retention (34.31%) than its nanoemulsion. The raloxifene nanoemulsion gel has no erythema and no eschar formation recorded, and it is safe for topical use. In the incision wound model in ovariectomized rats, breaking (898±25g) and tensile strengths (4.47±0.12 g/mm2) in raloxifene treated groups were found to be higher than the untreated control group. Additionally, in ovariectomized rats, wound contraction was found to be 100% in the treated group s following 20 days of post-wounding, where as in control group only 88% was contraction was observed. Also, more hydroxyproline content in raloxifene treated ovariectomized rat was observed that recommend more collagen content than the untreated ovariectomized rat but approximately similar effects to untreated non-ovariectomized rats. Histopathological studies confirmed that the raloxifene treated groups had more re-epithelialization, neo-vascularization, fibroblast proliferation, and collagen deposition than the control group. Conclusion: These results confirms that the raloxifene nanoemulsion gel has significant wound healing potential, as observed in ovariectomized rats, which will be helpful in postmenopausal cutaneous wound healing.
Keywords: Raloxifene; Nanoemulsion gel; Ovariectomized; Postmenopausal; Breaking; strength; Wound contraction; Hydroxyproline; Histopathology